2020
DOI: 10.1007/s40615-020-00832-5
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Maternal Healthcare Services Among Ethnic Minority Populations in Vietnam

Abstract: Background Previous studies have observed lower utilization of maternal healthcare services by ethnic minority groups in Vietnam compared with the majority Kinh community. This study sought to assess the utilization of maternal healthcare service-associated factors within 12 ethnic minority groups. Method The cross-sectional study enrolled 996 women from 12 ethnic minority groups in Vietnam in 2019. Women had pregnancy outcomes in the last 5 years. The two variables for maternal healthcare utilization were [1]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
2
2
0
1
Order By: Relevance
“…The educational level of women was the factor to receive four and above antenatal care visits. This finding was consistent with the study conducted in Amhara regional states, Ethiopia [29], Ethiopia [30], and Vietnam [31]. It showed that the increased educational level increases women's received optimal ANC visits.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The educational level of women was the factor to receive four and above antenatal care visits. This finding was consistent with the study conducted in Amhara regional states, Ethiopia [29], Ethiopia [30], and Vietnam [31]. It showed that the increased educational level increases women's received optimal ANC visits.…”
Section: Discussionsupporting
confidence: 91%
“…Women who were exposed to the media were more likely to use four and more ANC services than women who were not exposed to the media. This finding is similar to studies conducted in Ethiopia [30], Vietnam [31], and Tanzania [35]. Access to the media may have resulted in the more frequent use of ANC visits because the media may have offered relevant health promotion messages, such as the advantages of ANC and information on the danger signs of probable pregnancy problems [35].…”
Section: Discussionsupporting
confidence: 82%
“…Shaped by decades of structural deprivation and social exclusion, specific factors contributing to the profound MNCH disparities faced by ethnic minority populations are limited access to education, economic marginalization, remote and rural residence (where there are fewer and lower capacity health centers and a documented shortage of health workers [ 5 , 6 ]), limited access to MNCH information, low reproductive health knowledge, language barriers, and poor access to and uptake of perinatal care services [ 2 , 3 , 5 , 7 , 8 ]. A 2021 study found that economic marginalization and living over 5 km from the nearest health facility were associated with having fewer than 4 antenatal care visits [ 7 ]. Importantly, documented inequities along ethnic lines in health care seeking and utilization, MNCH, nutrition, and oral health and hygiene suggest that minority ethnicity alone is a critical determinant impacting health outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these barriers, the most prominent was physical access to healthcare services. In general, the further away a healthcare facility is, the less likely one is to use the services offered there [11,[19][20][21]. Poor infrastructure, which includes rugged terrain, poorly maintained roads, and a lack of public transportation facilities, also contributes to physical barriers to health service use by ethnic minority populations [7,8,11,12,14,17,18,21].…”
Section: Introductionmentioning
confidence: 99%